From Disks to Planets: The Making of Planets and Their Early Atmospheres. An Introduction - Lammer, Helmut; Blanc, Michel (Space science reviews, 2018)
This paper is an introduction to volume 56 of the Space Science Series of ISSI, “From disks to planets—the making of planets and their proto-atmospheres”, a key subject in our quest for the origins and evolutionary paths of planets, and for the causes of their diversity. Indeed, as exoplanet discoveries progressively accumulated and their characterization made spectacular progress, it became evident that the diversity of observed exoplanets can in no way be reduced to the two classes of planets that we are used to identify in the solar system, namely terrestrial planets and gas or ice giants: the exoplanet reality is just much broader. This fact is no doubt the result of the exceptional diversity of the evolutionary paths linking planetary systems as a whole as well as individual exoplanets and their proto-atmospheres to their parent circumstellar disks: this diversity and its causes are exactly what this paper explores. For each of the main phases of the formation and evolution of planetary systems and of individual planets, we summarize what we believe we understand and what are the important open questions needing further in-depth examination, and offer some suggestions on ways towards solutions. We start with the formation mechanisms of circumstellar disks, with their gas and disk components in which chemical composition plays a very important role in planet formation. We summarize how dust accretion within the disk generates planet cores, while gas accretion on these cores can lead to the diversity of their fluid envelopes. The temporal evolution of the parent disk itself, and its final dissipation, put strong constraints on how and how far planetary formation can proceed. The radiation output of the central star also plays an important role in this whole story. This early phase of planet evolution, from disk formation to dissipation, is characterized by a co-evolution of the disk and its daughter planets. During this co-evolution, planets and their protoatmospheres not only grow, but they also migrate radially as a result of their interaction with the disk, thus moving progressively from their distance of formation to their final location. The formation of planetary fluid envelopes (proto-atmospheres and oceans), is an essential product of this planet formation scenario which strongly constrains their possible evolution towards habitability. We discuss the effects of the initial conditions in the disk, of the location, size and mass of the planetary core, of the disk lifetime and of the radiation output and activity of the central star, on the formation of these envelopes and on their relative extensions with respect to the planet core. Overall, a fraction of the planets retain the primary proto-atmosphere they initially accreted from the gas disk. For those which lose it in this early evolution, outgassing of volatiles from the planetary core and mantle, together with some contributions of volatiles from colliding bodies, give them a chance to form a “secondary” atmosphere, like that of our own Earth. When the disk finally dissipates, usually before 10 Million years of age, it leaves us with the combination of a planetary system and a debris disk, each with a specific radial distribution with respect to their parent star(s). Whereas the dynamics of protoplanetary disks is dominated by gas-solid dynamical coupling, debris disks are dominated by gravitational dynamics acting on diverse families of planetesimals. Solid-body collisions between them and giant impacts on young planetary surfaces generate a new population of gas and dust in those disks. Synergies between solar system and exoplanet studies are particularly fruitful and need to be stimulated even more, because they give access to different and complementary components of debris disks: whereas the different families of planetesimals can be extensively studied in the solar system, they remain unobserved in exoplanet systems. But, in those systems, long-wavelength telescopic observations of dust provide a wealth of indirect information about the unobserved population of planetesimals. Promising progress is being currently made to observe the gas component as well, using millimetre and sub-millimetre giant radio interferometers. Within planetary systems themselves, individual planets are the assembly of a solid body and a fluid envelope, including their planetary atmosphere when there is one. Their characteristics range from terrestrial planets through sub-Neptunes and Neptunes and to gas giants, each type covering most of the orbital distances probed by present-day techniques. With the continuous progress in detection and characterization techniques and the advent of major providers of new data like the Kepler mission, the architecture of these planetary systems can be studied more and more accurately in a statistically meaningful sense and compared to the one of our own solar system, which does not appear to be an exceptional case. Finally, our understanding of exoplanets atmospheres has made spectacular advances recently using the occultation spectroscopy techniques implemented on the currently operating space and ground-based observing facilities. The powerful new observing facilities planned for the near and more distant future will make it possible to address many of the most challenging current questions of the science of exoplanets and their systems. There is little doubt that, using this new generation of facilities, we will be able to reconstruct more and more accurately the complex evolutionary paths which link stellar genesis to the possible emergence of habitable worlds.